RESECTIONOF A HORSESHOE KIDNEY IN A PATIENT WITH RENAL CELL CARCINOMA - K. M. Nyushko; M. A. Borisov; A. S. Kalpinskiy; B. Y. Alekseev; A. D. Kaprin (Исследования и практика в медицине)
Renal cell carcinoma (RCC) is one of the most urgent problems of modern urology, due to the steady increase in the incidence of this disease worldwide. Horseshoe kidney is a rare observation, the frequency of detection of this disease in the population is 2.8% of all malformations. RCC horseshoe kidney are rare, less than 2% of all cases of horseshoe kidney. Surgical treatment remains the golden standard of therapy of patients with RCC. The article presents a clinical case of resection of horseshoe kidney in a patient with RCC.